Ultra-Responses of Asphodelus tenuifolius L. (Wild Onion) and Convolvulus arvensis L. (Field Bindweed) against Shoot Extract of Trianthema portulacastrum L. (Horse Purslane) - Muhammad Shahid Hassan; Nargis Naz; Habib Ali; Basharat Ali; Muhammad Akram; Rashid Iqbal; Sidra Ajmal; Baber Ali; Sezai Ercisli; Kirill S. Golokhvast; Zeshan Hassan (Plants, 2023)
Weed infestation is a prime challenge coupled with lowering crop production owing to their competition with crop plants for available resources such as nutrients, water, space, moisture, and sunlight. Among weed control methods, the implementation of synthetic herbicides offers an instant solution for getting rid of weeds; however, they are a direct source of potential hazards for humans and generate resistance against synthetic weedicides, making them less effective. Allelopathy is something that happens in nature that can be used as a weed control method that increases crop yield and decreases dependency on synthetic chemicals. The mode of action of some phytochemicals corresponds to synthetic herbicides. Due to this feature, allelochemicals are used as bio-herbicides in weed management and prove more environmentally friendly than synthetic weedicides. The present investigation aims to assess the ultra-responses of A. tenuifolius and C. arvensis, while growing them in a pot experiment. Various levels of shoot extract (L2, L3, and L4) of T. portulacastrum along with the L1 (distilled water) and L5 (synthetic herbicide) were applied to the weeds. Results indicated that aqueous extracts of shoot of T. portulacastrum significantly (p ≤ 0.05) affect all the measured traits of weeds and their effects were concentration specific. All morphological parameters were suppressed due to biotic stress with an increase in free amino acids and calcium ions along with a decline in metaxylem cell area and cortical thickness in the root, while the vascular bundle area increased. The shoot extract intrusive with metabolisms corresponded with the synthetic herbicide. It is concluded that Trianthema shoot extract has a powerful phytotoxic impact on weeds (A. tenuifolius and C. arvensis) and can be used in bio-herbicide production.